Goethite–titania composite: disinfection mechanism under UV and visible light - Lara Rico, Rosalina; Múzquiz Ramos, Elia M.; López Badillo, Claudia M.; García Pérez, Ulises Matías; Cruz Ortiz, Brenda R. (2019)
Goethite–titania (a-FeOOH–TiO2) composites were prepared by co-precipitation and mechanical milling. The structural, morphological and optical properties of as-synthesized composites were characterized by X-ray powder diffraction, scanning electron microscopy and UV-Vis diffuse reflectance spectroscopy, respectively. a-FeOOH–TiO2 composites and TiO2-P25, as reference, were evaluated as photocatalysts for the disinfection of Escherichia coli under UV or visible light in a stirred tank reactor. a-FeOOH–TiO2 exhibited better photocatalytic activity in the visible region than TiO2-P25. The mechanical activation increased the absorption in the visible range of TiO2-P25 and the photocatalytic activity of a-FeOOH– TiO2. In the experiments with UV light and a-FeOOH–TiO2, mechanically activated, a 5.4 log-reduction of bacteria was achieved after 240 min of treatment. Using visible light the a-FeOOH–TiO2 and the TiO2-P25 showed a 3.1 and a 0.7 log-reductions at 240 min, respectively. The disinfection mechanism was studied by ROS detection and scavenger experiments, demonstrating that the main ROS produced in the disinfection process were superoxide radical anion, singlet oxygen and hydroxyl radical